The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jocb.387
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Creativity–Academic Achievement Relationship: A Study from China

Abstract: This study investigated gender differences in the relationship between creativity and academic achievement. A sample of 1082 primary students participated in this study in Beijing, China. Their age ranged between 8 and 15 years old (M = 10.41, SD = 0.99). Students’ creativity was measured by the Chinese version of the Torrance Test of Creative Thinking Figural Form A, and academic achievement was based on students’ self‐reported grades of last semester. Results revealed that there was a significantly positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
(77 reference statements)
2
16
0
2
Order By: Relevance
“…Karwowski et al (2020) reported that creativity is a strong predictor of math achievement when solving basic tasks but a constantly significant predictor of language tasks at any complexity level. This finding coincides slightly with Zhang et al (2018), who found that the correlation between creativity and achievement is stronger for language tasks than math tasks. Zhang et al (2018) hypothesized that the open-ended tasks in language classes could explain this difference.…”
Section: Creativity and Academic Achievementsupporting
confidence: 90%
See 2 more Smart Citations
“…Karwowski et al (2020) reported that creativity is a strong predictor of math achievement when solving basic tasks but a constantly significant predictor of language tasks at any complexity level. This finding coincides slightly with Zhang et al (2018), who found that the correlation between creativity and achievement is stronger for language tasks than math tasks. Zhang et al (2018) hypothesized that the open-ended tasks in language classes could explain this difference.…”
Section: Creativity and Academic Achievementsupporting
confidence: 90%
“…This finding coincides slightly with Zhang et al (2018), who found that the correlation between creativity and achievement is stronger for language tasks than math tasks. Zhang et al (2018) hypothesized that the open-ended tasks in language classes could explain this difference. Furthermore, Kim (2008) asserted that the relationship between academic achievement and creativity is weaker for higher creativity scores, especially when creativity is related to underachievement.…”
Section: Creativity and Academic Achievementsupporting
confidence: 90%
See 1 more Smart Citation
“…All predictive variables were normalized in each equation ( Garmezy et al, 1984 ). In addition, previous studies have shown that gender, age are important factors that influence volunteering behavior ( Warren et al, 2018 ; Zhang W. J. et al, 2018 ), therefore, the present study viewed gender and age were used as control variables.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to observed variable like gender moderating the relationship between creative thinking and academic performance, least is known as research works focused on other psychological variables different from those under investigation. For instance, studies such as Semordzi, Odame-Mensah, Hammond and Amoako [39], Zhang, Ren and Deng [40] and Ye, Posada, and Liu [41] used gender as moderator in relationship studies pairing personality traits against career choices and academic stress, gender difference in creativity and academic performance and academic self-efficacy. In terms of the Aboom Circuit located in the Cape Coast Metropolis, it is widely agreed that students' performance is usually appreciable for instance 50.21% of candidates who sat the BECE in 2015 passed their core subjects(English Language and Mathematics) (WAEC Chief Examiner's report as cited in [42]).…”
Section: Gender Difference Relationship Between Creative Thinking Acamentioning
confidence: 99%